Macroeconomic uncertainty and corporate capital structure: evidence from the Asia Pacific Region - Chow, Yee Peng; Junaina Muhammad; A.N. Bany-Ariffin; Cheng, Fan Fah (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of this paper is to examine the impact of macroeconomic uncertainty on corporate capital structure. This paper considers a wide spectrum of proxies for macroeconomic uncertainty to identify which types of macroeconomic uncertainty are important to the capital structure decisions of a sample of listed firms from seven Asia Pacific countries for the period 2004-2014. The regression models are estimated using the robust two-step system generalised method of moments (GMM) estimator. The results generally provide robust evidence of the negative effect of macroeconomic uncertainty on Asia Pacific firms’ capital structure using different proxies for macroeconomic uncertainty. When the aggregate data are split into developing and developed countries, this paper continues to find some evidence supporting the negative association between macroeconomic uncertainty and capital structure. The results also indicate that the three broad classifications of macroeconomic uncertainty, i.e., external sources of macroeconomic uncertainty, domestic sources of macroeconomic uncertainty, and volatility as a macroeconomic outcome, significantly affect corporate capital structure. Further analyses reveal that the capital structures of firms in the developing and developed countries are affected by different types of macroeconomic uncertainty. Hence, policy makers should strive to devise suitable course of actions to overcome the unfavourable outcomes stemming from the volatility in the macroeconomic environment, bearing in mind of the multidimensional aspects of macroeconomic uncertainty.